Strategies for engineering neural cell alignment and their biomedical applications - Nan Xia; Rui Liu; Weiwei Chen; Dandan Wang; Lingyun Sun (Engineered Regeneration, 2023)
Cell alignment plays a vital role in tissue regeneration, especially for neural cells like neurons. Recent progress in biomaterial technologies has enabled the creation of various approaches for engineering neural cell alignment, which has demonstrated significant effectiveness in several biomedical applications. This review primarily concentrates on the latest advancements for in vitro engineering of neural cell alignment. We also summarized their applications in biomedical research, particularly their potential in addressing nervous system injuries. Finally, we analyze the current challenges associated with engineering neural cell alignment and provide insights into future perspectives in this field.